The value of left atrial longitudinal strain in evaluating left atrial appendage spontaneous echo contrast in non-valvular atrial fibrillation - Ma, Chang sheng; Sun, Shi kun; Wang, Li; Zhou, Bing yuan; Dong, Feng lin (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Background: Spontaneous echo contrast (SEC) observed in transesophageal echocardiography (TEE) is a reliable predictor of the risk of future ischemic stroke in patients with non-valvular atrial fibrillation (NVAF). Left atrial strain globally reflects atrial function, remodeling and distensibility. The left atrial appendage (LAA) is a myogenic remnant of the left atrium, which can actively relax and contract. The left atrial appendage (LAA) is an important part of releasing the pressure of the left atrium. The key role of the left atrium is to regulate the left ventricular filling pressure, act as a reservoir for pulmonary venous return during ventricular contraction, and act as a conduit, transferring blood to the Left ventricle during early ventricular diastole. The purpose of this study was to explore the relationship between left atrial function and left atrial appendage spontaneous echo contrast (LAASEC). Methods: A retrospective study of 338 patients with non-valvular AF was conducted. Two-dimensional speckle-tracking echocardiography provided the following metrics of LA strain: LA strain during the reservoir phase (LASr), LA strain during the conduit phase (LAScd). LA or LAA has the dense SEC of more than grade 3, which is defined as mud like change or pre thrombosis. Results: Patients with level 3 SEC (n=81）has lower LASr than those with lower grades of SEC (n=257)( 7.20± 3.70 VS 17.48± 8.67,P<0.001). Multivariate logistic regression model showed that the type of atrial fibrillation (persistent~), increased heart rate, decreased LASr were independently associated with the dense LAASEC (OR(CI95%), 5.558(1.618~19.09), 1.016 (1.006~1.026) 0.002, 1.224 (1.085~1.381), both P<0.01). Venn Diagram showed that lower CHADVASC2 score groups had dense SEC cases. Receiver operating characteristic (ROC) curve was used for analyzing results and selecting cut off values. The cut off point for LASr < 8.85% and CHADVASC2 score was >2 scores with sensitivity and specificity were 79% and 85%. Conclusion: Lower LASr is independently associated with the dense LAASEC in NVAF and has incremental values superior to clinical scores . The decrease of LASr may be a potential non-invasive parameter for evaluating the higher risk of LAA thrombosis.